Evaluation of Antimicrobial and Antiviral Activities of Different Venoms - Kalayci, Sadik; Ustaoglu Iyigundogdu, Zeynep; M. Yazici, Muge; A. Asutay, Burcin; Demir, Okan; Sahin, Fikrettin (Infectious Disorders - Drug Targets, 2016)
Background: Animals’ venomous secretions or peptides obtained from those secretions are used in the development of new therapeutic agents. The aims of this study were to investigate antimicrobial and antiviral activity of four different venoms obtained from the frog named Bufo arenarum and the snakes Crotalus atrox, Causus rhombeatus and Naja melanoleuca. Methods: Antimicrobial activities of the venoms tested against 9 bacteria, 1 yeast, 1 fungal species and 2 viral species based on micro-well dilution assay and antiviral assay. Results: Four different venoms were examined to evaluate the antimicrobial and antiviral activity against 9 bacteria, 1 yeast and 1 fungal and 2 viral species. None of the venoms exhibited anticandidal or antifungal activity. However, all of the four venoms tested were found to have both antibacterial and antiviral activities. Conclusion: This is the first study demonstrating that venoms of Crotalus atrox and Bufo arenarum have antibacterial activities against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumannii, Bacillus subtilis, Aeromonas hydrophila, Aeromonas spp. Antiviral activities of 4 venoms against Poliovirus and Adenovirus were also investigated for the first time.
Keywords: frog